An Analysis of Financial Feasibility on the Batik Tulis Lasem "SR" - Tutik Khotimah; Nanik Ermawati; Ratih Nindyasari (Enrichment : Journal of Management, 2020)
Batik Tulis Lasem is one of the Micro, Small and Medium Enterprises (MSMEs) in Indonesia. This study aims to determine whether the investment in additional capital for Batik Tulis Lasem Sumber Rejeki (SR) is feasible to run. The research method used in this study uses quantitative methods using numbers determined based on the feasibility of a business with non-discounted techniques, namely Payback Period (PP), Break Even Point (BEP) and non-discounted techniques using the Net Present Value (NPV) technique, Internal Rate of Return (IRR). The data sources used in this study are primary and secondary data sources. The results showed that the results of testing using the BEP, PP, NPV and IRR methods in accordance with the business feasibility criteria, the Batik Tulis Lasem “SR” were eligible to be taken by means of credit through the banking system.